Strategi Rekrutmen Pendidik dan Tenaga Kependidikan dalam Penempatan Kerja di SMK Al-Islam Surakarta - Sofia Dian Adelia; Nuzul Arijannah; Erliyana Dewi Saraswati; Faizar Aulia Rachman (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
Recruitment is the process of producing a group of qualified applicants for organizational jobs. The objectives of the study are: 1) To determine the implementation of teacher recruitment at SMK Al Islam Surakarta. 2) To find out the implementation of educator selection at SMK Al-Islam Surakarta. 3) To know the process of placing educators at SMK Al Islam Surakarta. Researchers use qualitative research methods with a qualitative descriptive approach, the data collection techniques used in this study are structured interviews and indirect observation. Data validity techniques use triangulation methods. The results of the study are as follows: 1) The recruitment strategy of educators and educators as well as job placement at SMK Al-Islam Surakarta is to promote internally and externally, then carry out several stages of selection, including administrative tests, interview tests and teaching tests in class (microteaching). 2) The role of the school in the implementation of this recruitment and selection as a provider of human resources, which is then submitted to the foundation for selection. 3) The placement of educators and education personnel is adjusted to their educational background, work experience and according to their fields, so that educators and educators can perform the work given optimally.